2022
DOI: 10.1097/jd9.0000000000000204
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acne Inversa (Hidradenitis Suppurativa) in China: A Nationwide Cross-Sectional Epidemiological Study

Abstract: Objective: This study was performed to estimate the prevalence of hidradenitis suppurativa (HS) in China and describe the demographic and clinical features of HS in the Chinese population. Methods: This multicenter clinic-based cross-sectional study was conducted in dermatology clinics within 19 hospitals located in 15 cities/provinces across China from September to October 2020. The prevalence of HS was calculated as the percentage of patients with HS among all visitors at participating clinics during the 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…
Hidradenitis suppurativa (HS), also known as acne inversa, is a chronic inflammatory skin disease that mainly affects apocrine-bearing areas, with a prevalence rate of 0.03%-1.2% worldwide. 1,2 It severely affects the patient's social, working and psychological quality of life in a manner that significantly exceeds that of psoriasis and other skin diseases. 3 Cumulating data have shown that the pathogenesis of HS is multifactorial and involves immunology, bacterial colonization, hormones, genetics, etc.
…”
mentioning
confidence: 99%
“…
Hidradenitis suppurativa (HS), also known as acne inversa, is a chronic inflammatory skin disease that mainly affects apocrine-bearing areas, with a prevalence rate of 0.03%-1.2% worldwide. 1,2 It severely affects the patient's social, working and psychological quality of life in a manner that significantly exceeds that of psoriasis and other skin diseases. 3 Cumulating data have shown that the pathogenesis of HS is multifactorial and involves immunology, bacterial colonization, hormones, genetics, etc.
…”
mentioning
confidence: 99%